Effects of whole-body vibration on bone mineral density in postmenopausal women: an overview of systematic reviews - Shao Yin; Ying Liu; Yue Zhong; Fengya Zhu (BMC, 2024)
Abstract Objective The aim of this study is to evaluate the findings of existing systematic reviews (SRs) and provide scientific evidence on the efficacy and safety of whole-body vibration (WBV) in improving bone mineral density (BMD) in postmenopausal women, to provide recommendations and guidance for future high-quality clinical research and SRs. Methods We conducted searches in six databases (SinoMed, CNKI, Cochrane Library, Embase, PubMed, Web of Science) from the inception of the databases until July 31, 2023. The language was limited to Chinese or English. The methodological quality, risk of bias, and evidence grade of outcomes were evaluated using AMSTAR-2, ROBIS, and GRADE, respectively. Additionally, the degree of overlap in randomized controlled trials (RCTs) among the SRs was calculated using corrected covered area (CCA). Furthermore, we performed quantitative synthesis or descriptive analysis of the relevant data. All relevant operations were independently conducted by two individuals. Results A total of 15 SRs were included in the analysis, out of which three were qualitative descriptions and 12 were meta-analyses. According to AMSTAR-2, only two SRs were rated as low or moderate, while the remaining 13 SRs were rated as critically low quality. The ROBIS assessment indicated that seven SRs had a low risk of bias, while 8 SRs had a high risk of bias. The overall findings suggest that WBV does not have a significant advantage in improving BMD in postmenopausal women. Furthermore, the CCA results revealed a high overlap in RCTs across five outcomes among the 15 SRs. Only five SRs reported specific adverse reactions/events experienced by participants after WBV interventions, and none of the SRs reported any severe adverse events. Conclusion The existing evidence cannot establish definitive advantages of WBV in improving BMD in postmenopausal women. Therefore, we do not recommend the use of WBV for improving BMD in postmenopausal women. However, WBV may have potential value in maintaining BMD in postmenopausal women, further research is needed to confirm these findings.